A Prison within a Prison: Segregation of HIV Positive Inmates and Double Stigma - Gaskin, Emily Hilyer (2009)
Although the majority of state prison systems have made the move away from segregated housing for HIV positive inmates, a few still continue this practice. The purpose of this study was to learn more about the experiences of women who have carried the double stigma of being HIV positive prisoners who were segregated within the prison system because of their illness. Drawing on interviews with HIV positive women who served time in a segregated facility and are now released, I was able to explore how double stigma and segregation affect identity and daily life. By asking these women questions about their experiences as inmates who were further segregated because of their HIV status, I call attention to the strong association between power, authoritative knowledge, and policy